Fortified Ultra-Processed Foods as an Intervention in Vulnerable Populations to Address Nutrient Deficiencies: A Mini Review - Fadly, Khaerul; Chaerunnisa , Novia Nurul (Jurnal Gizi dan Pangan, 2023)
This review aimed to examine review papers on effects of Ultra-Processed Foods (UPFs) on vulnerable groups, specifically malnourished children. While some studies showed negative health effects of UPFs, others showed that UPFs were beneficial. For example, fortified biscuits improved nutrient levels in primary school children and ready-to-use therapeutic foods helped malnourished children. Overall, it is crucial to balance the potential benefits and risks of UPFs. Therefore, policymakers should adopt a multifaceted approach that includes redefinition, reformulation, regulation, and education about the mindful consumption of UPFs.